Second language acquisition : an introductory course - Gass, Susan M.; Plonsky, Luke; Behney, Jennifer (Routledge, 2020)
"Now in a fifth edition, this bestselling introductory textbook remains the cornerstone volume for the study of second language acquisition (SLA). Its chapters have been fully updated, and reorganized where appropriate, to provide a comprehensive yet accessible overview of the field and its related disciplines. To reflect current developments, new sections and expanded discussions have been added. The fifth edition of Second Language Acquisition retains the features that students found useful in previous editions. This edition provides pedagogical tools that encourage students to reflect upon the experiences of second language learners. As with previous editions, discussion questions and problems at the end of each chapter help students apply their knowledge, and a glossary defines and reinforces must-know terminology. This clearly-written, comprehensive, and current textbook, by Susan Gass, Jennifer Behney, and Luke Plonsky, is the ideal textbook for the introductory SLA course in second language studies, applied linguistics, linguistics, TESOL, and language education programs"--